The composite nature of physical geography: Moving from linkages to integration. (February 2014) - Malanson, George P.; Scuderi, Louis; Moser, Katrina A.; Willmott, Cort J.; Resler, Lynn M.; Warner, Timothy A.; Mearns, Linda O.
This editorial is the product of the Progress in Physical Geography lecture at the April 2013 meeting of the Association of American Geographers. The paper was presented by George Malanson, the North American Editor, and the co-authors presented critiques based on a draft. Subsequently, the manuscript was developed and revised based on discussion at the meeting and additional exchange among the co-authors.